The Influence of Mathematical Thinking Ability with Modified MOORE Method on Learning Outcomes of Basic Mathematic II Chemical Education Students - Susda Heleni; Zulkarnain Zulkarnain (Journal of Educational Sciences, 2018)
Developing the ability of absolute thinking is needed in mathematic class where the subject has a characteristic as a branch of science which the object of study is abstract-natured and related with a pattern of thinking. Basic mathematics is one of the courses that can develop student’s ability to think. The results acquired by the students are still not maximized; this is because the students struggle to develop their own knowledge to form concepts. Student’s activities in the learning process are only skill-natured in solving problems. One of the learning methods that can be implemented is the Modified Moore method. This research aims to discover the effects of mathematical thinking capabilities with the Modified Moore Method towards the learning achievement of Basic Mathematic II of Chemistry study program from the FKIP of Universitas Riau in the even semester of 2013/2014 academic year. The form of this research is a quasiexperimental research. The experiment design used in this research is the Single Group Pretest/Posttest Design which includes Quasi Experimental Design without control group. The population in this research is the students of Chemistry study program from the FKIP of Universitas Riau in the even semester of 2013/2014 academic year. The sample of this research is all students of Chemistry study program from the FKIP of Universitas Riau in the even semester of 2013/2014 academic year consisting 36 peoples. The sample is obtained through purposive sampling technique. Based on data analysis using t test on mathematical thinking capabilities by applying modified Moore Method, it was found that students scores during post test is better than pre-test. The influences of mathematical thinking capabilities with modified Moore Method of the results learning mathematics basic II Chemistry Education in second semester academic year 2013/2014 is equal to 98,85%. It can be concluded that there is an influence on the mathematical thinking capabilities by applying Modified Moore Method towards the students learning achievement of Basic Mathematic II of Chemistry study program from the FKIP of Universitas Riau in the even semester of 2013/2014 academic year.